Feeding blend optimization for livestock by using goal programming approach / Nur Rasyida Mohd Rashid ... [et al.] - Mohd Rashid, Nur Rasyida; Mohd Lip, Norliana; Mohd Salim, Fatin Farhayu; Kamazan, Nurullisa Faranajwa; Mohd Latib, Siti Nor Asfarina (Universiti Teknologi MARA, 2020)
Feed blend formulation is an important process in the livestock industry. This process will help the livestock industry nowadays to keep providing continuous supply of animal protein food to cater for the expanding and increasing demand as Malaysia is undergoing a rapid growth in economic and human population. The formulation of feed blend involves multiple objectives to be achieved through the decision making process. In this project, Goal Programming (GP) method is used to formulate the livestock feed blend for a farm situated in Negeri Sembilan, Malaysia. This method is an approach of assisting the decision makers to solve multiple objectives for livestock feed blend in determining an optimal combination of ingredients to meet the nutritional requirements. This will lead to a rational use of available resources by minimizing the production cost and maximizing the nutritional value required for the growth of livestock. The nutrition for the livestock contains dry matter (DM), metabolism energy (ME), crude protein (CP) and crude fibre (CF). Then, the preemptive model is tested using LINGO software and the results have been validated by using Mean Absolute Percentage Error (MAPE). All of the multiple objectives have been fully achieved which represents the ability of the goal programming model to comply with optimizing the feed blend formulation.